2016
DOI: 10.1002/jobm.201500555
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of cadmium bioaccumulation and enhancing cadmium tolerance in Pichia kudriavzevii by sodium chloride preincubation

Abstract: Application of growing microorganisms for cadmium removal is limited by the sensitivity of living cells to cadmium. The effects of sodium chloride (NaCl) preincubation on the cadmium bioaccumulation and tolerance of Pichia kudriavzevii and Saccharomyces cerevisiae were investigated in this study. NaCl preincubation significantly reduced the intracellular and cell-surface cadmium bioaccumulation of P. kudriavzevii at both 6 and 20 mg L(-1) cadmium, while no obvious effect was observed in S. cerevisiae except th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…cerevisiae . Ma et al reported that NaCl preincubation could enhance cadmium resistance by lowering cadmium uptake instead of promoting cadmium efflux. Our research broadened the application of preincubation.…”
Section: Discussionmentioning
confidence: 99%
“…cerevisiae . Ma et al reported that NaCl preincubation could enhance cadmium resistance by lowering cadmium uptake instead of promoting cadmium efflux. Our research broadened the application of preincubation.…”
Section: Discussionmentioning
confidence: 99%